Implementation of a clinical pathway for the surgical treatment of colorectal cancer during the COVID‐19 pandemic. (17th August 2020) - Evans, S.; Taylor, C.; Antoniou, A.; Agarwal, T.; Burns, E.; Jenkins, J.T.; Miskovic, D.
Abstract: Aim: This report summarizes the early experience of implementing elective colorectal cancer surgery during the COVID‐19 pandemic. Methods: A pathway to minimize the risk of including COVID‐19‐positive patients for elective surgery was established. Prioritization and additional safety measures were introduced into clinical practice. Minimal invasive surgery was used where appropriate. Results: Thirty‐eight patients were prioritized, and 23 patients underwent surgery (eight colon, 14 rectal and one anal cancer). The minimal invasive surgery rate was 78%. There were no major postoperative complications or patients diagnosed with COVID‐19. Histopathological outcomes were similar to normal practice. Conclusion: A safe pathway to offer standard high‐quality surgery to colorectal cancer patients during the COVID‐19 pandemic is feasible.